Questionnaire «Opioid anosognosia» is a new tool for assessment anosognosia in opioid-dependent patients - R. D. Ilyuk; E. A. Granovskaya; V. V. Bocharov; D. I. Gromyko; A. I. Nechaeva; V. V. Pushina; A. Ya. Wuks; E. M. Krupitsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2025)
The absence of reliable, valid, and widely accepted measurement tools hinders the study of opioid anosognosia. The aim of this study: to develop, validate, and standardize a self-report questionnaire for the rapid and comprehensive assessment of opioid anosognosia. Statistical analyses confirmed the questionnaire’s reliability and validity, showing its accuracy in assessing opioid anosognosia and enhancing comprehension of this complex phenomenon. Materials and Methods. The study included 92 patients with opioid dependence syndrome (F11.20; F11.21). The mean age of the participants was 39.95 (SD = 4.7) years, the duration of opioid dependence was 11.3 (SD  =  7.0) years, and the mean age of onset of dependence was 14.0 (SD  =  6.0) years. Results. The structure of the questionnaire was developed, and statements for seven subscales were defined: unawareness, denial of symptoms of the disease, overall disease denial, denial of the consequences of the disease, emotional non-acceptance of the disease, disagreement with treatment, and non-acceptance of sobriety.The psychometric properties of the questionnaire were analyzed, including external criterion validity, testretest reliability, and internal consistency. A standardization procedure for the questionnaire was conducted, and average empirical values were determined for each subscale. Opioid-dependent individuals were found to have moderate to elevated levels of anosognosia. Conclusions. The developed diagnostic tool for assessing anosognosia in opioid dependence is a novel, validated, and standardized clinical-psychological diagnostic questionnaire. This methodology enables a comprehensive diagnosis of the level of anosognosia across its individual components and the creation of a profile of opioid anosognosia. It can be noted that anosognosia is a complex multidimensional phenomenon, which is one of the characteristic manifestations of opioid dependence.